DISTRIBUTION PATTERN AND DENSITY OF Holothuria atra IN TELUK TEMPURUNG WATERS, BUKIT TAMBUN TULANG VILLAGE, BATANG KAPAS PESISIR SELATAN DISTRICT, WEST SUMATERA - Oktafiandi Oktafiandi; Eni Sumiarsih; Muhammad Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractSea cucumber is a species that has high economic value if it is used properly.The habitat that sea cucumbers tend to prefer is the bottom of the water with a substrate of mud or sand, such as those in Teluk Tempurung, Bukit Tambun Tulang Village.To find out the level of preference for an organism to its habitat, it is necessary to look at the distribution pattern of the organism it self. This research aims to determine the distribution and density ofHolothuria atra and also it’s ecological condition of Teluk Tempurung. The method used in this research  is a swept area (area sweeping) which is called a belt transect.This method was used to observe biota in a certain area. There are 3 transects for sea cucumber observation with a transect length of 50 meter, on each transect there are 3 plots measuring 5x5 meter. Observations were made in three repetitions. The type of sea cucumber found in the waters of Teluk Tempurung is Holothuria atra with a density ranging from 0.329 to 0.404 (organisms/ m2). Based on the research results, it can be concluded that the distribution pattern of Holothuria atra in Teluk Tempurung, Bukit Tambun Tulang Village is clustered. Keywords: Substrate, Seagrass Meadows, Coral Reefs, Habitat.